(untitled) (Altre Modernità, 2021)
Contemporary art that turns its attention to investigating the geopolitical situation of today’s world has long worked on the visible and invisible boundaries that separate people, societies and cultures. The production on the theme of the reification of transnational borders through physical barriers (such as walls) or natural barriers (such as the sea) is now vast both for the quantity of works produced and for the heterogeneity of the forms in which it expresses itself. For the seriousness of the consequences of their management on the people who try to cross them and for the scope of the discourses that, initially local, prove to be potentially universal, two areas represent emblematic cases: the border between Mexico and the United States and the Mediterranean basin. Contemporary art focuses on these areas as well, with contributions that often resonate with those from other disciplines (anthropology, border studies). Referring to some of the works realized there in the last twenty years, some recurrences will be identified in the speeches promoted (denunciation of contingent situations, criticism of colonialism harbinger of current discriminations, analogies that connect human beings beyond their cultural variability), coming to identify the final common denominator of these works in the will to question and break down not only the walls, but also the borders, seen as remnants of colonial ways of relationship between human beings no longer acceptable.